Maintenance eculizumab dose adjustment in the treatment of atypical hemolytic uremic syndrome: a case report and review of the literature. Issue 8 (6th July 2016) - Thomson, Nick; Ulrickson, Matthew
Key Clinical Message: Atypical hemolytic uremic syndrome (aHUS) patients treated with eculizumab may require higher doses to achieve and maintain optimal clinical response. Further studies are warranted to elucidate optimal dosing regimens of eculizumab in aHUS patients, and whether dosing regimens can be predicted based on mutational status, eculizumab levels, or other testing. Abstract : Atypical hemolytic uremic syndrome (aHUS) patients treated with eculizumab may require higher doses to achieve and maintain optimal clinical response. Further studies are warranted to elucidate optimal dosing regimens of eculizumab in aHUS patients, and whether dosing regimens can be predicted based on mutational status, eculizumab levels, or other testing.